A Crossover Comparative Study to Assess Efficacy of 5% vs. 20% Albumin in the Treatment of Anasarca in Children with Idiopathic Nephrotic Syndrome - Garg, Ajoy Kumar; Kalra, Suprita; Kumar, Ashutosh; Kanitkar, Madhuri (Journal of Nepal Paediatric Society, 2020)
Introduction: Co-administration of albumin and furosemide has shown better response than furosemide alone in managing anasarca among children with nephrotic syndrome. There are different concentrations of albumin available. The aim of this study was to compare diuretic response to co-administration of either 5% or 20% albumin with furosemide in these children. Methods: It was a crossover randomised trial conducted on children with nephrotic syndrome with moderate to severe oedema at a tertiary care centre. They were randomised to two groups; Group A (n = 14) received 5% albumin along with furosemide in midway followed by 20% albumin after washout period of 48 hrs and group B (n = 10) received albumin vice versa. Baseline and post therapy vitals, fluid intake, urine output and biochemistry were noted. Primary outcomes were increase in urine output and reduction in weight following co-administration of albumin with furosemide. For analysis of primary outcomes, two interventional arms were formed; group I (5% Albumin co-administered with furosemide) and group II (20% albumin co-administered with furosemide). Results: Total children were 24 in each arm i.e. group I and II. Eighteen (75%) were males. Mean (range) age at enrolment and duration of illness were 55.3 (15 - 144) and 18.6 (1 - 120) months respectively. Mean difference (SD) in urine output were 1.52 (1.11) and 1.66 (0.95) ml/kg/hr (p = 0.12) and mean percentage weight loss were 2.25% (2.12) and 3.68% (3.84) in group I and II respectively (p = 0.64). On further comparing, urine output was significantly better when 5% albumin was co-administered with furosemide during first period than in second period. Conclusions: Co-administration of either 5% or 20% albumin with furosemide is equally safe and effective in increasing urine output in children with anasarca.